Australian labour force participation: Historical trends and future prospects - Linus Gustafsson (The Australian Government, The Treasury, 2021)
Over the past 40 years, Australia has experienced significant changes to the proportion of the population that is attached to its labour market. From the early 1980s, the aggregate labour force participation rate rose steadily, climbing from around 60 per cent in 1983 to almost 66 per cent in 2011. Underlying this long-term increase in the aggregate participation rate are opposing developments for males and females. The male participation rate fell from close to 80 per cent in the late 1970s to just above 70 per cent in recent years. Yet this decline in male participation rates over this period has been more than offset by an increase in female participation rates. Since the 1970s, the female participation rate has increased by more than 15 percentage points. This paper studies these developments through the lens of an age and cohort-based framework and uses the estimated model to analyse historical trends and the implications of these past developments for future participation rate trends in Australia.
Keywords: E17; E24; E27; J21; J22; 330; Labour force; Labour Force Composition; Labour Force Demographics; Size of Labour Force; Labour Force Participation; Labour Supply